Letter to Leona Hudson from Dugald Hudson, Korea, August 20, 1957 - Hudson, Dugald (Valdosta State University Archives and Special Collections, 1957)
Letter to Leona Hudson from Dugald Hudson, Korea, August 20, 1957. To: Hudson, Leona (Valdosta, GA) From: Hudson, Dugald (Korea) Names in the Letter: Boyles, F.R.; Gen. I.D. White; Stacy, Millie; Col. Martz; Bookers, Ted Description: Included with letter is a photo taken by a Japanese boy, of Dugald walking down a street in Tokyo, and later mailed to him Original Label: 12.
1 Electronic record(s) and derivatives. 1 pages. 1514765 bytes. MD5: 38BBE26286AD8BF8B9A2035389EBBFBB
Keywords: Hudson, Dugald; Letters; Hudson, Leona; Korean War (1950-1953)